In Situ Atomic‐Scale Observation of Reversible Potassium Storage in Sb2S3@Carbon Nanowire Anodes. (20th September 2020) - Cheng, Yong; Yao, Zhenpeng; Zhang, Qiaobao; Chen, Jiamin; Ye, Weibin; Zhou, Shiyuan; Liu, Haodong; Wang, Ming‐Sheng
Abstract: Antimony trisulfide‐based materials have drawn growing attention as promising anode candidates for potassium‐ion batteries (PIBs) because of their high capacity and good working potential. Despite the extensive investigations on their electrochemical properties, the fundamental reaction mechanisms of Sb2 S3 anodes, especially the reaction kinetics, structural changes, and phase evolutions, remain controversial or even largely unknown. Here, using in situ transmission electron microscopy, the entire potassiation–depotassiation cycles of carbon‐coated Sb2 S3 single‐crystal nanowires are tracked in real time at the atomic scale. The potassiation of Sb2 S3 involves multistep reactions including intercalation, conversion, and two‐step alloying, and the final products are identified as cubic K2 S and hexagonal K3 Sb. These findings are confirmed by density functional theory calculations. Interestingly, a rocket‐launching‐like nanoparticle growth behavior is observed during alloying reactions, which is driven by the K + concentration gradient and release of stress. More impressively, the potassiated products (i.e., K3 Sb and K2 S) can transform into the original Sb2 S3 phase during depotassiation, indicating a reversible phase transformation process, as distinct from other metal chalcogenide based electrodes. This work reveals the detailed potassiation/depotassiation mechanisms of Sb2 S3 ‐based anodes and can facilitate the analysis of the mechanisms of other metal chalcogenide anodes in PIBs. Abstract : The atomic‐scale potassiation/depotassiation mechanisms of Sb2 S3 @carbon nanowires are investigated using an in situ transmission electron microscopy and density functional theory calculations. The potassiation involves multistep reactions including intercalation, conversion, and two‐step alloying featured by the growth of K‐Sb alloying nanoparticles that resembles the launching of a rocket. Impressively, the phase transformations are reversible during depotassiation, distinct from other metal chalcogenide‐based electrodes.